Effects of opening arterial roads in exclusive residential subdivisions - Diaz, Crispin Emmanuel D. (1995)
Exclusive residential villages are planned residential subdivisions which are comprised of single-detached housing units, and for which access is for residents only. Urbanization leads to an increasing need for additional capacity in the existing road networks. Village size, shape and location are the most important aspects of interaction with the road system. When villages conflict with the function of the primary road system, opening of these villages is a very visible option for increasing network capacities. Unfortunately there has been a lack of careful consideration of the effects of such moves on residents of these villages, and whether or not such action would necessary abate the decline in performance of the road traffic system. This paper sought to identify the most important benefits of exclusiveness or conversely to identify the most serious benefits of its loss. From the village inventory, around 16.18 percent of all residential villages in Metro Manila village inventory are exclusive, affecting a large number of households. The surveys identify security and clean, quiet environment as the most important benefit of exclusiveness.
Computer print-out.
Thesis (M.S.)--University of the Philippines, Diliman.
Keywords: Villages -- Access roads -- Philippines -- Manila metropolitan area; Roads -- Philippines -- Manila metropolitan area; Transportation -- Philippnes -- Manila metropolitan area